Monetary policy transmission and firms' financial constraints (2018)
I test the relationship between monetary policy and firms' financial constraints. Since financial constraints are inherently unobservable, I estimate a corporate finance model to infer the shadow cost of external finance for Colombian firms during 2004-2015. The results show that monetary policy, through changes in the real intervention interest rate, has a significant positive comovement with Colombian firms' financial constraints. Complementary evidence suggests that firms with higher collateral and higher debt-to-assets ratio suffered larger increases in their shadow value of external finance after a monetary contraction. By contrast, after a monetary tightening, firms paying dividends and with high cash flow were the least constrained.